A Cosmovisão dos moradores do Povoado Passarinho em relação aos indígenas apinajé da aldeia prata em Tocantinópolis-TO - Feitosa, Lara Hanna Ribeiro (Universidade Federal do Tocantins, 2019)
The present Course Conclusion Paper aims to investigate the Worldview of the inhabitants of the Passarinho Village, in relation to the Apinajés peoples, considering the proximity of the village to the Silver Village both located in the municipality of Tocantinópolis-TO. The methodology adopted was autobiographical research. using for interviewee data collection narrative interviews as a way to validate the speech of the subjects. The narrative interview aims to stimulate and even even encourage the interviewed subject to tell something about important event in your life and social context by asking generator. It is important to mention that non-indigenous people living in in the Passarinho community and those who live within the Silver Village. The interview had focus on investigating their view of the Apinajé culture through their intercultural relations. Thus, the results show that the residents of the bird village do not show a few misguided thoughts about the Silver Village Indians.